EFEKTIVITAS PERAN PERAWAT TERHADAP PELAKSANAAN PROMKES PADA PENDERITA HIPERTENSI DI WILAYAH KERJA PUSKESMAS TANDANG BUHIT KECAMATAN BALIGE KABUPATEN TOBA SAMOSIR TAHUN 2017 - Tiarnida Nababan (Jurnal Keperawatan Priority, 2018)
Health promotion can affect a person in having knowledge and motivation about health sciences, including healthy and regular way of life. The role of nurse who have obtained information or knowledge through health education can also have positive values, attitudes and motivations in implementing matters relating to the maintenance, rescue and treatment of hypertensive disease. The purpose of this study was to determine the effectiveness of the role of nurses in conducting health promotion on the people with hypertension in the work area of Tandang Buhit Health Unit of Balige District, Toba Samosir Regeancy in 2017. This type of research is an analytic survey with cross sectional design. The population in this research is all patients hypertension in Puskesmas Tandang Buhit Unit of Balige District as many as 42 people. The sampling technique in this research is determined by total sampling technique as many 42 people. The result of chi square test based on the degree of significance was (α) = 0,05 and df = 1 and the calculation result showed that X2 count 9,732 > X2 table 3,841. It can be conclude Ho was rejected. Ha was accepted. The conclusion from the research stated that there is a correlation between mother’s knowledge that the relation of effectiveness of the role of nurses in conducting health promotion on the people with hypertension in the work area of Tandang Buhit Health Unit of Balige District, Toba Samosir Regeancy in 2017. It is expected for nurse to apply education to hypertension patients with better so symptom and prevention of hypertension event can applied properly.